Chemerin Regulates the Proliferation and Migration of Pulmonary Arterial Smooth Muscle Cells via the ERK1/2 Signaling Pathway - Peng, Linqian; Chen, Yunwei; Li, Yan; Feng, Panpan; Zheng, Yan; Dong, Yongjie; Yang, Yunjing; Wang, Ruiyu; Li, Ailing; Yan, Jianghong; Shang, Feifei; Tang, Ping; et al. (Frontiers in Pharmacology, 2022)
Pulmonary arterial hypertension (PAH) is an incurable disease with high mortality. Chemerin has been found to be associated with PAH. However, the specific role of chemerin in mediating PAH development remains unclear. This study aimed to elucidate the regulatory effects and the underlying mechanism of chemerin on PAH and to investigate the expression levels of chemerin protein in plasma in PAH patients. In vivo, a PAH animal model was established in rats by monocrotaline (MCT) injection. We found that the expression levels of chemerin and its receptor, chemokine-like receptor 1 (CMKLR1), were significantly upregulated in the lungs of PAH rats. Primary cultured pulmonary arterial smooth muscle cells (PASMCs) were exposed to hypoxia or treated with recombinant human chemerin, we found that CMKLR1 expression was upregulated in PASMCs in response to hypoxia or chemerin stimulation, whereas the exogenous chemerin significantly promoted the migration and proliferation of PASMCs. Notably, the regulatory effects of chemerin on PASMCs were blunted by PD98059 (a selective ERK1/2 inhibitor). Using enzyme linked immunosorbent assay (ELISA), we found that the protein level of chemerin was also markedly increased in plasma from idiopathic pulmonary arterial hypertension (IPAH) patients compared to that from healthy controls. Moreover, the diagnostic value of chemerin expression in IPAH patients was determined through receiver operating characteristic (ROC) curve analysis and the result revealed that area under ROC curve (AUC) for plasma chemerin was 0.949. Taken together, these results suggest that chemerin exacerbates PAH progression by promoting the proliferation and migration of PASMCs via the ERK1/2 signaling pathway, and chemerin could be a promising noninvasive diagnostic biomarker for PAH.